CHALLENGES OF TAKING MALAY LANGUAGE COMMUNICATION COURSE AMONG INTERNATIONAL STUDENTS IN TERTIARY LEVEL OF STUDIES - Suhaila Ngadiron; Azureen Abd Aziz; Muhamad Rusly, Nurien Hidayu (INTERNATIONAL JOURNAL OF HUMANITIES, PHILOSOPHY AND LANGUAGES (IJHPL), 2024)
This study was conducted to identify the challenges faced by tertiary students to converse and communicate using the Malay language in their tertiary learning. Data obtained were based on a few observations conducted on 100 students who took the Malay Language Communication course. Students were asked to video-record their daily communication with local students using Malay language. Then, the data obtained from the observations would be presented via presentation in class. Based on the feedback received, there are three major challenges faced by these international students that include; mother tongue destruction, student attitude, and environmental issues. Few recommendations are presented based on the research findings.